2008
DOI: 10.1002/ajmg.b.30699
|View full text |Cite
|
Sign up to set email alerts
|

Association of the serotonin transporter polymorphism and obsessive‐compulsive disorder: Systematic review

Abstract: We investigated the association between the long (l) and short (s) alleles of the serotonin transporter polymorphism (5-HTTLPR) in the promoter region of the SLC6A4 gene and obsessive-compulsive disorder (OCD) using meta-analysis to combine all published data from case-control and family based association studies (2,283 cases). In stratified meta-analysis we investigated whether age of sample (child and adult), ethnicity (Caucasian and Asian) and study design (case-control and family-based association studies)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 54 publications
2
61
1
2
Order By: Relevance
“…The 10R allele of STin2 has been associated with lower transcriptional activity than the 12R allele (Fiskerstrand et al, 1999). Earlier studies Hu et al, 2006;Kim et al, 2005;McDougle et al, 1998) and a recent review (Bloch et al, 2008b) reported that the l allele of 5-HTTLPR was a risk factor for OCD while some other studies reported that the s allele was a risk factor (Lin, 2007;Perez et al, 2006). As mentioned early, interactions of SLCA64 by gender on OCD (Dickel et al, 2007;Voyiaziakis et al, 2011) and OCPD (Blom et al, 2011), were also reported.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The 10R allele of STin2 has been associated with lower transcriptional activity than the 12R allele (Fiskerstrand et al, 1999). Earlier studies Hu et al, 2006;Kim et al, 2005;McDougle et al, 1998) and a recent review (Bloch et al, 2008b) reported that the l allele of 5-HTTLPR was a risk factor for OCD while some other studies reported that the s allele was a risk factor (Lin, 2007;Perez et al, 2006). As mentioned early, interactions of SLCA64 by gender on OCD (Dickel et al, 2007;Voyiaziakis et al, 2011) and OCPD (Blom et al, 2011), were also reported.…”
mentioning
confidence: 86%
“…The estimated heritability for OCD ranges from 0.45 to 0.65 for children and adolescents and from 0.27 to 0.47 for adults in twin and family studies (van Grootheest et al, 2005), indicating that early-onset OCD may have a different etiology (including genetic factors) from late-onset OCD. Molecular genetic association studies have specifically provided further evidence for the genetic contributions of SLC6A4 to OCD (Bloch et al, 2008b;Hu et al, 2006;Lin, 2007;Voyiaziakis et al, 2011). SLC6A4 transports serotonin from the synaptic cleft to presynaptic neurons, thereby attenuating current serotonin neurotransmission while also maintaining the pool of available serotonin for subsequent release (Lesch and Gutknecht, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SLC6A4 gene is involved in serotonin reuptake at the synapses and variation of this gene has been linked to various psychiatric disorders, including OCD. 60 A functional promoter polymorphism, 5-HTTLPR, has been extensively studied. The resulting alleles differ in transcriptional activity, with the short (S-) allele linked to lower expression of the gene than the long (L-) allele.…”
Section: Obsessive-compulsive Disorder (Ocd)mentioning
confidence: 99%
“…This may explain the inconsistent results obtained from case-control association studies of this polymorphism. 60 With regards to the serotonin receptor genes: (i) the genotype distribution of the 5-HT1Db G861C polymorphism differed significantly between Afrikaner OCD patients and healthy controls, with more C-homozygotes observed in this patient subgroup 51 , and, (ii) interestingly, although variants in the 5-HT2A gene were not found to be associated with OCD in the abovementioned studies, the T-allele of the T102C variant was found to be associated with trichotillomania in South African patients. 56 Trichotillomania is a psychiatric disorder that is characterised by repetitive pulling of hair, which may have a biological overlap with OCD.…”
Section: Obsessive-compulsive Disorder (Ocd)mentioning
confidence: 99%